Souvenir Purchasing System - Adibah , Ahmud Puat @ Ahmad Fuat (UTeM, 2009)
Souvenir Purchasing System (SPS) is a web-based system development project. The primary purpose to develop this system is to enable the customers to buy the products of A&Y Marketing and Resources's company via online as before this, they only buy the products in a manual method. The system will be used by the staff of the company and the customers who to buy the souvenirs. This system encircles online catalogue module, user authentication module, shopping cart module and payment process module. All of these modules will cover all the process of purchasing the souvenirs' products. Beside that, this system can also backup and recover the data from the database. To develop this system, SSADM approach is used and SDLC model had been chosen as a methodology. Results get from this application development is hoped to give the ability for the customers to buy souvenirs in a digitized way.